1996
DOI: 10.1071/ar9960047
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for manipulating the vegetative-reproductive balance in horticultural crops through nitrogen nutrition: a review

Abstract: This review examines the prospects for manipulating the vegetative-reproductive balance in horticultural crops through nitrogen (N) nutrition. It also examines whether incorrect timing or excessive applications of N stimulate vegetative growth at the expense of reproductive growth. Productivity of horticultural crops is dependent on an adequate N status because photosynthetic capacity is dependent on leaf N content per unit area. Efficient N uptake occurs during periods of active growth and depends on active p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 60 publications
1
27
1
4
Order By: Relevance
“…This control may be dependent upon the availability of N in the form of ammonium or on the demand for C molecules such as 2-oxoglutarate at particular physiological stages of the plant or under different stress conditions during which there is a shortage of carbohydrates (Robinson et al 1991;Aubert et al 2001). For example, it has been observed that changes in the endogenous C/N ratio promote both flowering and fruiting (Kinet et al 1985;Huett 1996). One can therefore hypothesise that co-operative action between cytosolic GS and GDH in the phloem vascular tissue would be of particular importance in the control of the synthesis of trafficking C and N metabolites.…”
Section: Discussionmentioning
confidence: 98%
“…This control may be dependent upon the availability of N in the form of ammonium or on the demand for C molecules such as 2-oxoglutarate at particular physiological stages of the plant or under different stress conditions during which there is a shortage of carbohydrates (Robinson et al 1991;Aubert et al 2001). For example, it has been observed that changes in the endogenous C/N ratio promote both flowering and fruiting (Kinet et al 1985;Huett 1996). One can therefore hypothesise that co-operative action between cytosolic GS and GDH in the phloem vascular tissue would be of particular importance in the control of the synthesis of trafficking C and N metabolites.…”
Section: Discussionmentioning
confidence: 98%
“…Nutrient demand of fruit near maturity is more likely to be reflected in a reduction in leaf nutrient composition if trees are under nutrient stress. Fruit compete effectively with other tree components for nutrients (and carbohydrates) to the extent of reducing vegetative growth (Huett 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, like other fruit crops, in citrus, N is applied through soil application. However, ef fi cacy of soil-applied N is affected by many unrelated factors, and also there is always risk of groundwater pollution (Albrigo 1999 ;Huett 1996 ) . Hence, urea applied as a foliar spray is rapidly absorbed by citrus leaves (Ali and Lovatt 1992 ) .…”
Section: Foliar Application Of Nitrogenmentioning
confidence: 99%